FANATISME KELOMPOK SUPORTER SEPAK BOLA BALI UNITED - Wirasmara, I Gede Bayu; Suka Arjawa, I Gusti Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This thesis discusses the fanaticism of Bali United FC supporters namely Semeton Dewata. Bali United FC is a team based in Dipta Gianyar Stadium which has many supporters. The form of fanatism Semeton Dewata is in the form of singing in the stadium, choreography is an art attraction in the form of drawings or writing, and purchase tickets as a form of love to the team. Causes of fanaticism include Regional Context, Environment, and Mass Media. The purpose of this research is to answer the problem by using qualitative research method. The theory used is Weber's Rational Action Theory, among others, value rationality, instrumental rationality, affective rationality, tradiosional rationality. Based on the result of this research, Semeton Dewata shows its fanatism to positive thing. Keywords: Bali United, Fanatisme